2008
DOI: 10.1093/pcp/pcn106
|View full text |Cite
|
Sign up to set email alerts
|

Roles of RCN1, Regulatory A Subunit of Protein Phosphatase 2A, in Methyl Jasmonate Signaling and Signal Crosstalk between Methyl Jasmonate and Abscisic Acid

Abstract: Methyl jasmonate (MeJA) as well as abscisic acid (ABA) induces stomatal closure with their signal crosstalk. We investigated the function of a regulatory A subunit of protein phosphatase 2A, RCN1, in MeJA signaling. Both MeJA and ABA failed to induce stomatal closure in Arabidopsis rcn1 knockout mutants unlike in wild-type plants. Neither MeJA nor ABA induced reactive oxygen species (ROS) production and suppressed inward-rectifying potassium channel activities in rcn1 mutants but not in wild-type plants. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
82
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 26 publications
5
82
0
Order By: Relevance
“…These results are consistent with our previous results, i.e., NO is involved in both MeJA-and ABA-induced stomatal closure and functions downstream of the branching point of MeJA and ABA signaling in Arabidopsis guard cells. 7 Our finding implies that protein phosphatase 2A might positively regulate NO levels in guard cells (Fig. 2).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…These results are consistent with our previous results, i.e., NO is involved in both MeJA-and ABA-induced stomatal closure and functions downstream of the branching point of MeJA and ABA signaling in Arabidopsis guard cells. 7 Our finding implies that protein phosphatase 2A might positively regulate NO levels in guard cells (Fig. 2).…”
mentioning
confidence: 52%
“…5 NO mediates elevation of cytosolic free Ca 2+ concentration ([Ca 2+ ] cyt ), inactivation of inward-rectifying K + channels and activation of S-type anion channels, 6 which are known to be key factors in MeJA-and ABA-induced stomatal closure. 2,[7][8][9] It has been reported that ROS was not induced by MeJA and ABA in the MeJA-and ABA-insensitive mutant, rcn1 in which the regulatory subunit A of protein phosphatase 2A, RCN1, is impaired. 7,10 We examined NO production induced by MeJA and ABA in rcn1 guard cells (Fig.…”
mentioning
confidence: 99%
“…The rcn1-1 mutant was impaired in abscisic acid-induced stomatal closing and showed reduced abscisic acid-induced calcium increases. Whereas in wild-type seedlings both methyl jasmonate and abscisic acid induce stomatal closure, neither did the rcn1-1 mutant seedlings (Saito et al, 2008). The retardation of phot2 dephosphorylation in the rcn1-1 mutant described above could account for these results.…”
Section: Discussionmentioning
confidence: 90%
“…Both methyl jasmonate and abscisic acid normally induce a burst of reactive oxygen species and activate inward-rectifying potassium channels (Saito et al, 2008). However, the hormones fail to do either in the rcn1-1 mutant, suggesting that RCN1 functions upstream from reactive oxygen species production and membrane depolarization but downstream from the two growth regulators.…”
Section: Discussionmentioning
confidence: 99%
“…8) For whole-cell current recordings, the pipette solution contained 30 mM KCl, 70 mM K-Glu, 2 mM MgCl 2 , 3.35 mM CaCl 2 , 6.7 mM EGTA, 10 mM HEPES adjusted to pH 7.1 with Tris, and the bath solution contained 30 mM KCl, 2 mM MgCl 2 , 40 mM CaCl 2 , and 10 mM MES titrated to pH 5.5 with Tris. 9) For data analysis, pCLAMP 8.2 software (Molecular Devices, Sunnyvale, CA) was used.…”
mentioning
confidence: 99%